2022
DOI: 10.3346/jkms.2022.37.e9
|View full text |Cite
|
Sign up to set email alerts
|

Association of Early Pubertal Onset in Female Rats With Inhalation of Lavender Oil

Abstract: Background Central precocious puberty (CPP) is caused by early activation of the hypothalamic–pituitary–gonadal axis but its major cause remains unclear. Studies have indicated an association between chronic environmental exposure to endocrine-disrupting chemicals and pubertal onset. Essential oil is widely used in homes worldwide for relief of respiratory symptoms, stress, and/or sleep disturbance. Methods To evaluate this association, we compared the hormone levels an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Indeed, the authors thought that the mechanism of action was probably through olfactory stimulation of the hypothalamus, rather than a hormonal effect. 28 In contrast to the above studies showing no in vivo oestrogenic effect of LO, Slighoua and co-workers reported an increase in uterine weights and serum E 2 levels of female rats treated with hydro-ethanolic extracts of Lavandula officinalis Chaix. 29 These extracts contained phenolic compounds, but it is unknown whether they also contained linalool or linalyl acetate, as found in LO.…”
Section: In Vitro and Non-human In Vivo Studies Of Lo's And Tto's Oes...mentioning
confidence: 86%
See 2 more Smart Citations
“…Indeed, the authors thought that the mechanism of action was probably through olfactory stimulation of the hypothalamus, rather than a hormonal effect. 28 In contrast to the above studies showing no in vivo oestrogenic effect of LO, Slighoua and co-workers reported an increase in uterine weights and serum E 2 levels of female rats treated with hydro-ethanolic extracts of Lavandula officinalis Chaix. 29 These extracts contained phenolic compounds, but it is unknown whether they also contained linalool or linalyl acetate, as found in LO.…”
Section: In Vitro and Non-human In Vivo Studies Of Lo's And Tto's Oes...mentioning
confidence: 86%
“…1 Along with the three initial patients described by Henley et al, an additional nine patients who were reported to use a product containing LO or TTO were subsequently diagnosed with either prepubertal gynaecomastia (total n=8) or premature thelarche (n=4) (Table 2). 1,2,[27][28][29] Three of the eight boys had Tanner genitalia staging, and all were stage 1. Eight of the twelve children also had Tanner pubic hair staging.…”
Section: Reports Of Prepubertal Gynaecomastia and Premature Thelarche...mentioning
confidence: 99%
See 1 more Smart Citation